2021
DOI: 10.1016/j.chom.2021.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive mapping of mutations in the SARS-CoV-2 receptor-binding domain that affect recognition by polyclonal human plasma antibodies

Abstract: The evolution of SARS-CoV-2 could impair recognition of the virus by human antibody-mediated immunity. To facilitate prospective surveillance for such evolution, we map how convalescent plasma antibodies are impacted by all mutations to the spike’s receptor-binding domain (RBD), the main target of plasma neutralizing activity. Binding by polyclonal plasma antibodies is affected by mutations in three main epitopes in the RBD, but longitudinal samples reveal the impact of these mutations on antibody binding vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

61
1,240
3
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 1,099 publications
(1,309 citation statements)
references
References 82 publications
61
1,240
3
5
Order By: Relevance
“…We applied a previously described deep mutational scanning approach to comprehensively map mutations in the SARS-CoV-2 RBD that escape binding from antibodies [15,18,19]. Briefly, this method involves displaying nearly all amino-acid mutants of the SARS-CoV-RBD on the surface of yeast [20], incubating the yeast with an antibody or antibody cocktail, using fluorescence-activated cell sorting (FACS) to enrich functional RBD mutants that escape antibody binding (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We applied a previously described deep mutational scanning approach to comprehensively map mutations in the SARS-CoV-2 RBD that escape binding from antibodies [15,18,19]. Briefly, this method involves displaying nearly all amino-acid mutants of the SARS-CoV-RBD on the surface of yeast [20], incubating the yeast with an antibody or antibody cocktail, using fluorescence-activated cell sorting (FACS) to enrich functional RBD mutants that escape antibody binding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To enable more comprehensive and prospective assessment of the impacts of viral mutations, we recently developed a method to completely map how all single amino-acid mutations in the SARS-CoV-2 RBD affect antibody binding [15,18,19]. These maps enable immediate interpretation of the consequences of new mutations and systematic comparison of escape mutations across antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…66 This illuminating study demonstrated that escape sites from antibodies can be constrained with respect to their effects on expression of properly folded RBD and ACE2 binding, suggesting that escape-resistant antibody cocktails can compete for binding to the same RBD region but have different escape mutations which limits the virus ability to acquire novel sites of immune escape in the RBD without compromising its binding to ACE2. 66 Comprehensive mapping of mutations in the SARS-CoV-2 RBD that affect recognition by polyclonal human serum antibodies revealed that mutations in E484 site tend to have the largest effect on antibody binding to the RBD, 67 and various functional neutralization assay experiments indicated that E484 modifications can reduce the neutralization potency by some antibodies by >10 fold. [67][68][69] These studies also indicated that K417N and N501Y mutants can escape neutralization by some monoclonal antibodies but typically only modestly affected binding.…”
Section: Sars-cov-2 S Protein Between a Spectrum Of Closed And Receptmentioning
confidence: 99%
“…66 Comprehensive mapping of mutations in the SARS-CoV-2 RBD that affect recognition by polyclonal human serum antibodies revealed that mutations in E484 site tend to have the largest effect on antibody binding to the RBD, 67 and various functional neutralization assay experiments indicated that E484 modifications can reduce the neutralization potency by some antibodies by >10 fold. [67][68][69] These studies also indicated that K417N and N501Y mutants can escape neutralization by some monoclonal antibodies but typically only modestly affected binding. 67,70 At the same time, mutations in the epitope centered around E484 position (G485, F486, F490) or in the 443-455 loop (K444, V445, L455, F456 sites) strongly affected neutralization for several Abs.…”
Section: Sars-cov-2 S Protein Between a Spectrum Of Closed And Receptmentioning
confidence: 99%
See 1 more Smart Citation